1999
DOI: 10.1037/0033-295x.106.4.748
|View full text |Cite
|
Sign up to set email alerts
|

Noun-phrase anaphora and focus: The informational load hypothesis.

Abstract: The processing of noun-phrase (NP) anaphors in discourse is argued to reflect constraints on the activation and processing of semantic information in working memory. The proposed theory views NP anaphor processing as an optimization process that is based on the principle that processing cost, defined in terms of activating semantic information, should serve some discourse function--identifying the antecedent, adding new information, or both. In a series of 5 self-paced reading experiments, anaphors' functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
299
9
31

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(369 citation statements)
references
References 44 publications
18
299
9
31
Order By: Relevance
“…Grammatical subjects in English are often the first-mentioned entity in an utterance, but not always, and both positions have been shown to impact reference resolution when unconfounded (see Kaiser & Trueswell, in press). Other relevant features of the discourse are the thematic roles of recently mentioned referents, parallelism of the syntactic roles of anaphors and antecedent, and information carried by focus constructions, like clefts (e.g., Almor, 1999;Arnold, 2001;Arnold, Eisenband, et al, 2000;Ariel, 1990;Givón, 1983;Sanford & Garrod, 1981;Stevenson, et al, 1994; see Arnold, 1998, for a review). A referent that is highly accessible in an addressee's discourse representation does not require as specific a referential expression as a new referent does, so effects of discourse status can be interpreted as evidence that speakers aim to produce expressions that are optimally interpretable.…”
mentioning
confidence: 99%
“…Grammatical subjects in English are often the first-mentioned entity in an utterance, but not always, and both positions have been shown to impact reference resolution when unconfounded (see Kaiser & Trueswell, in press). Other relevant features of the discourse are the thematic roles of recently mentioned referents, parallelism of the syntactic roles of anaphors and antecedent, and information carried by focus constructions, like clefts (e.g., Almor, 1999;Arnold, 2001;Arnold, Eisenband, et al, 2000;Ariel, 1990;Givón, 1983;Sanford & Garrod, 1981;Stevenson, et al, 1994; see Arnold, 1998, for a review). A referent that is highly accessible in an addressee's discourse representation does not require as specific a referential expression as a new referent does, so effects of discourse status can be interpreted as evidence that speakers aim to produce expressions that are optimally interpretable.…”
mentioning
confidence: 99%
“…As we will see below, these are features that contribute to referent prominence. Generally speaking, entities that the linguistic context has made especially prominent are more likely to be realized as pronouns by speakers, and are more easily identified as referents for pronouns by listeners, than are less prominent referents (e.g., Almor, 1999;Ariel, 2001;Fletcher, 1984;Gundel, Hedberg, and Zacharski, 1993;Prince, 1992, among many others). Less prominent referents tend to be invoked by more explicit linguistic forms.…”
Section: Introductionmentioning
confidence: 99%
“…Results from numerous psycholinguistic experiments have shown that anaphor resolution is greatly determined by semantic factors (e.g., Dell, McKoon, & Ratcliff, 1983;Garnham, Oakhill, & Cain, 1997;McKoon & Ratcliff, 1980;O'Brien, Raney, Albrecht & Rayner,1997; for reviews, see Almor, 1999;Ariel, 1990;Garnham, 2001;Myers & O'Brien, 1998;Garrod & Sanford, 1994;Gernsbacher, 1989;Sanford & Garrod, 1989). For example, readers experience difficulties in resolving anaphors that are more specific than their antecedent (e.g., ''A bird would sometimes wander into the house.…”
Section: Introductionmentioning
confidence: 99%